Faktor-Faktor yang Berhubungan dengan Pencegahan Demam Berdarah Dengue (DBD) - Dwi Anna Nurkhasanah; Rico Januar Sitorus; Heru Listiono (Universitas Batanghari Jambi, 2021)
The factors related to the prevention of dengue include knowledge, attitudes, and the role of health workers. clean and healthy lifestyle (PHBS), education, knowledge, attitudes, motivation and the environment. One of the efforts that can be done is by implementing 3M plus, namely burying, draining, and giving abate powder and burning the remains of garbage. The purpose of this study was to determine the relationship between knowledge, attitudes and roles of health workers simultaneously with the prevention of Dengue Hemorrhagic Fever (DHF) at Simpang Babat Public Health Center in Pali Regency in 2020. This study used a quantitative analytical study method with a cross-sectional research approach, with the number of a sample of 51 respondents. The results showed that there was a relationship between knowledge, attitudes and the role of health workers simultaneously on the prevention of DHF.